Analyzing and enhancing compliance and regulatory affairs in HR: a comprehensive study on policy adherence and legal frameworks - Fuad (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2023.